2007
DOI: 10.1111/j.1464-410x.2007.06859.x
|View full text |Cite
|
Sign up to set email alerts
|

Venous thromboembolism and cyproterone acetate in men with prostate cancer: a study using the General Practice Research Database

Abstract: nested case-control study design amongst all men with advanced prostate cancer, qualified by evidence of hormonal treatment. RESULTSThe time between diagnosis and first treatment was significantly shorter for men first treated with CPA than for men first treated with a luteinizing hormone releasing hormone (LHRH) analogue (adjusted hazard ratio 1.33, 95% confidence interval, CI, 1.06-1.67). When the first treatment was CPA, the treatment-free period after diagnosis was significantly shorter for men who later h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 24 publications
(24 reference statements)
0
9
1
2
Order By: Relevance
“…Seaman et al compared the risk of venous thromboembolism among patients treated with different antiandrogens and LHRH agonists. The group found that venous thromboembolism was associated only with cyproterone acetate, whereas the other antiandrogens did not contribute to thromboembolic event 17. In our series, ADT users presented a significantly higher percentage of lower leg fracture/surgery than the non-ADT users (6.30% vs 5.27%, p<0.01).…”
Section: Discussioncontrasting
confidence: 46%
“…Seaman et al compared the risk of venous thromboembolism among patients treated with different antiandrogens and LHRH agonists. The group found that venous thromboembolism was associated only with cyproterone acetate, whereas the other antiandrogens did not contribute to thromboembolic event 17. In our series, ADT users presented a significantly higher percentage of lower leg fracture/surgery than the non-ADT users (6.30% vs 5.27%, p<0.01).…”
Section: Discussioncontrasting
confidence: 46%
“…The aim of internal validation is to separate uncertain from true cases based on information from Lungenembolie). Um in der GPRD Patienten mit dem bestätigten akuten Ereignis von anderen Patienten abgrenzen zu kön-nen, d. h. also zur Diagnosesicherung, wurde in mehreren Arbeiten neben der geführten Diagnose als zusätzliches Kriterium das Vorliegen einer Coumarin-Verschreibung genutzt [10,11,12]. Problematisch kann ein solches Vorgehen aber dann sein, wenn ein akutes Ereignis gehäuft zu letalen Verläufen führt: Hier würde dann eine ambulante Verschreibung des Zielarzneimittels natürlich nicht mehr erfolgen, das zusätzliche Kriterium in der Datenbank also nicht mehr erscheinen.…”
Section: Validation Of Secondary Data Strengths and Limitations Abstunclassified
“…Um diesem Problem zu begegnen, haben einige Autoren z. B. bei venösen thromboembolischen Ereignissen als Einschlusskriterium auch den Tod aufgrund eines solchen Ereignisses in ihre Falldefinition aufgenommen [10,11] oder alternativ zur Coumarin-Verschreibung als Zusatzkriterium eine verzeichnete Hospitalisierung gefordert [12].…”
Section: Validation Of Secondary Data Strengths and Limitations Abstunclassified
“…VTE occurred more frequently in breast cancer patients randomized to tamoxifen than in those on placebo, anastrozole, or exemestane, respectively, and the incidence of ATE was higher for tamoxifen than that of either anastrozole or letrozole [42][43][44][45][46][47][48]. That noted, a metaanalysis calculated the absolute excess incidence of DVT, PE, and CVA in tamoxifen-treated patients as only 0.037%, 0.038%, and 0.267%, respectively [43].…”
Section: Treatment Factorsmentioning
confidence: 99%
“…In a study of palliative cyproterone acetate (CPA), LHRH analogs, estrogen, and non-steroidal antiandrogens for prostate cancer, VTE was a hazard with all of these agents. However, CPA was significantly more thrombogenic than anti-androgens (OR 3.46; 95% CI: 1.91-6.25) or LHRH analogs (OR 3.35; 95% CI: 2.38-4.72) [48].…”
Section: Treatment Factorsmentioning
confidence: 99%